2009
DOI: 10.1111/j.1399-3038.2008.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of parent‐reported food hypersensitivities and food allergies among children aged 1–4 yr

Abstract: Food allergies (FAs) and hypersensitivities (FHSs) have rarely been studied in large unselected child populations. This population-based cross-sectional survey estimated the occurrence of FHS as perceived by parents and that of FA diagnosed by a physician among children aged 1-4 yr in south-eastern Finland. Before the scheduled annual follow-up visit to the local child health clinic, the parents of children who were born between 1 April, 2001 and 31 March, 2005, and living in the Province of South Karelia (dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 35 publications
(100 reference statements)
6
78
2
1
Order By: Relevance
“…More prevalent symptoms of bronchial asthma, allergic rhinitis and atopic dermatitis in 6 -7 years boys and in 13 -14 years girls were also determined in Kaunas, Lithuania [21,22], more prevalent home allergies among boys than girls were found out in Vilnius [23]. More prevalent food allergy among boys than girls was also found in Finland [24].…”
Section: Discussionmentioning
confidence: 95%
“…More prevalent symptoms of bronchial asthma, allergic rhinitis and atopic dermatitis in 6 -7 years boys and in 13 -14 years girls were also determined in Kaunas, Lithuania [21,22], more prevalent home allergies among boys than girls were found out in Vilnius [23]. More prevalent food allergy among boys than girls was also found in Finland [24].…”
Section: Discussionmentioning
confidence: 95%
“…However, considering the previously shown large discrepancies between parent-reported and diagnosed food allergies (2,(4)(5)(6)(7)(8)(9)16,17), and the fact that many children on special medical diets lack medical certificates, some children may have been subjected to unnecessarily restricted diets. A potential way to avoid this may be the requirement for mandatory medical certificates for special diets for medical reasons, preferably with an appropriate time limit, for example for cows' milk and hens' egg allergies.…”
Section: Discussionmentioning
confidence: 99%
“…There are large discrepancies between parent-reported and physician-diagnosed food hypersensitivity, which might lead to unnecessary diet restrictions with potential negative effects on nutrition during an important period of growth and development (2,(4)(5)(6)(7)(8)(9)(16)(17)(18)(19). Unnecessary special diets can also result in additional costs and efforts for families and the preschools and schools their children attend (20).…”
Section: Introductionmentioning
confidence: 99%
“…A Finnish study reports a combined lifetime prevalence of FA perceived by parents only and FA diagnosed by a physician of 30% among 1-to 4-year-old children. 18 A UK study reported a cumulative incidence of 26% for parental-perceived FA by 1 year of age and 34% for 3-year-old children, whereas the incidences of FA confirmed by controlled food challenges and "a clear convincing clinical history" were 3% and 5%, respectively. 19 Added to the impact of pediatric FA on public health, the number of children with FA seems to be increasing.…”
Section: Introductionmentioning
confidence: 99%